And the dead shall rise the murder of Mary Phagan and the lynching of Leo Frank - Oney, Steve (New York Vintage, 2013)
On April 27, 1913, the bludgeoned body of thirteen-year-old Mary Phagan was discovered in the basement of Atlanta?s National Pencil Factory. The girl?s murder would be the catalyst for an epic saga that to this day holds a singular place in America?s collective imagination?a saga that would climax in 1915 with the lynching of Leo Frank, the Cornell-educated Jew who was convicted of the murder. The case has been the subject of novels, plays, movies and even musicals, but only now, with the publication of And the Dead Shall Rise, do we have an account that does full justice to the mesmerizing and previously unknown details of one of the most shameful moments in the nation?s history.
Includes index